Implants as anchorage for the correction of localized dental malocclusion: a retrospective clinical study - Hu, Ying-Wen; Zeng, Yin-Xin; Zhang, Yu-Xuan; Lai, Peng-Yu; Liang, Ran; Chen, Yi-Qi; Huang, Hai; Guo, Guan-Sheng (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundTooth loss accompanied by adjacent tooth inclination or rotation presents a biomechanical challenge in combined orthodontic–implant rehabilitation. Whether “implant-first anchorage” provides superior clinical efficiency and biological benefits compared with the conventional “orthodontics-first then implant” pathway remains uncertain.MethodsA retrospective cohort study was conducted based on cases treated between January 2019 and December 2024 by the Departments of Implantology and Orthodontics at the Affiliated Stomatological Hospital of Jinan University. Patients with partial edentulism and localized malalignment were allocated into two cohorts according to the actual treatment pathway received: implant-first (n = 20) versus orthodontics-first (n = 20). Clinical data were extracted from medical records and radiographs. Primary outcomes included treatment duration, cost, and patient-reported satisfaction (VAS). Secondary outcomes comprised periodontal parameters (mPLI, SBI, PD), adjacent tooth inclination, alveolar crest height, and number of visits.ResultsCompared with the orthodontics-first cohort, the implant-first cohort showed a markedly shorter time for local alignment (5.00 ± 1.25 vs. 11.78 ± 2.35 months, P < 0.001), lower overall cost (3,000.00 ± 0.00 vs. 6,100.00 ± 680.56 RMB, P < 0.001), fewer visits (8.20 ± 1.32 vs. 15.10 ± 2.49, P < 0.001), and higher satisfaction (8.05 ± 1.32 vs. 6.10 ± 1.68, P < 0.001). Periodontal metrics were consistently more favorable in the implant-first cohort (mPLI 1.20 ± 0.36 vs. 3.05 ± 0.50; SBI 0.96 ± 0.46 vs. 1.89 ± 0.39; PD 2.09 ± 0.37 vs. 2.67 ± 0.33; all P < 0.01). Changes in adjacent tooth inclination and space gain were comparable between cohorts (P > 0.05). Alveolar crest resorption was lower in the implant-first cohort (0.36 [0.06, 0.85] vs. 1.25 [0.54, 2.24] mm, P = 0.012).ConclusionWhen appropriately indicated, an implant-first anchorage pathway yields superior efficiency, lower cost, and better periodontal conditions compared with the conventional orthodontics-first approach, without compromising space control or tooth movement quality.